Factor Analysis on New Normal Medical Services during COVID-19’s Outbreak in Out Patient Department of Health Care Provider under Ministry of Public Health - Nawsuwan, Kittiporn; Singweratham, Noppcha (Princess of Naradhiwas University Journal, 2023)
This quantitative research aimed to investigate factor analysis on new normal of medical services during COVID-19’s outbreak in out patient department of Health care provider under Ministry of Public Health. The samples were 3,200 medical professionals working under the Ministry of Public Health, recruited by multi-stage random sampling. The questionnaire was used to collect data through google form with its validity ranging from .67-1.00 and its Cronbach’s alpha coefficient reliability at .967. Data were analyzed using Exploratory Factor Analysis (EFA), and the factor extraction was performed by principal component analysis using factor rotation in form of orthogonal rotation with varimax. The results were found as follows: The new normal of medical services during COVID-19’s Outbreak in Out patient department consisted of 5 components and 32 indicators. The 5 components included 1) Environmental management with 8 indicators, 2) Use of personal protective equipment and action plan with 12 indicators, 3) Administrative management with 5 indicators, 4) Facility with 3 indicators, and 5) Warning sign with 5 indicators. The 5 components and 32 indicators received a cumulative percentage variance at 66.73 which had Eigen value presented at 20.02, 2.24, 1.77, 1.41 and 1.25, respectively.